Dose formation and hematologic effects with prolonged internal exposure of rats by isotope 131I - E. A. Sova; I. P. Drozd (Ядерна фізика та енергетика)
Processes in single dose formation and long-term domestic revenue 131I in rats was investigated. Original method of estimating absorbed doses in hemacyte for makrodozimetric indicators was proposed. Dose factors for hemacyte and the dynamics of the blood-forming organs doses for prolonged two cases of prolonged exposure was calculated. Hematologic effects were studied for two variants of entry of the isotope. Peculiarities of doses formation and identified hematological effects are discussed.